Universidad Nacional Mayor de San Marcos’s History. Three stages and two illustrious people - Casalino Sen, Carlota (2018)
This article examines, firstly, the model of university that followed the National University of San Marcos when it was created. Second, it identifies the stages through which its history can be better understood. The first stage responds to its role played during the process of conquest and colonization of the Viceroyalty of Peru; The second stage corresponds to the role of San Marcos during the construction of the nation-state in the second half of the nineteenth century in the context of economic growth associated with the guano boom; And the third stage is associated with the university reform of Cordoba, when students and teachers are incorporated into the decisionmaking and university management bodies. Finally, in the third place, the role of two illustrious figures is analyzed: Fray Tomás de San Martín as founder of the University and José Antonio Encinas as one of the main promoters of the third democratizing stage.